Professional outcome of medical graduates: a 17 year cross-sectional study from India - Pandey, Avinash; Mishra, Richa; Markandeywar, Neeraj (International Journal Of Community Medicine And Public Health, 2017)
Background: In India, long term data regarding professional outcomes and geographical distribution of enrolled medical graduates is lacking. This adversely impacts policy for efficient healthcare delivery. Methods: A cross sectional survey of students enrolled as medical graduates in year 2001 was done at single point follow up after 17 years. Along with demographic data, gender, seat quota, post-graduate qualification, type of practice, discipline of choice and current geographic locations were collected. Logistical regression model with odds ratio was used to analyse association between variables. Results: 192/200 medical graduates were analysed. Male: female ratio was 119: 73. 109 (56%) had post-graduate degree, 35 (18%) had post-graduate diploma, while another 24 (12.8%) completed super-specialty degree.125 (65%) completed post-graduation in clinical disciplines. 103 (54%) are serving government institutes. 54 (28%) practice in metro cities, while 48 (25%) are in non-metro capital urban locations. Only 44 (23%) are serving rural Indian population, while 17 (9%) are at foreign countries. General medicine (12.5%), obstetrics (8%), paediatrics (8%) anaesthesia (7%) and general surgery (6.7%) were the most common broad clinical specialities. Females had high likelihood to pursue obstetrics/ gynaecology {OR-11.4 (95%CI-2.6-48.7)}; while males were more likely to select medical {OR-0.54 (95% CI-0.25-1.0)} and surgical disciplines {OR- 0.42 (95% CI-0.18-0.98)}. Conclusions: Majority of medical graduates complete post-graduation courses, with preference for clinical disciplines. Less than one fourth of doctors serve rural population.